Transforming growth factor-β1 genotype and susceptibility to chronic obstructive pulmonary disease. Issue 2 (3rd February 2004) - Wu, L; Chau, J; Young, R P; Pokorny, V; Mills, G D; Hopkins, R; McLean, L; Black, P N
Abstract : Background: Only a few long term smokers develop symptomatic chronic obstructive pulmonary disease (COPD) and this may be due, at least in part, to genetic susceptibility to the disease. Transforming growth factor β1 (TGF-β1 ) has a number of actions that make it a candidate for a role in the pathogenesis of COPD. We have investigated a single nucleotide polymorphism at exon 1 nucleotide position 29 (T→C) of the TGF-β1 gene that produces a substitution at codon 10 (Leu→Pro). Methods: The frequency of this polymorphism was determined in 165 subjects with COPD, 140 healthy blood donors, and 76 smokers with normal lung function (resistant smokers) using the polymerase chain reaction and restriction enzyme fragment length polymorphism. Results: The distribution of genotypes was Leu-Leu (41.8%), Leu-Pro (50.3%), and Pro-Pro (7.9%) for subjects with COPD, which was significantly different from the control subjects (blood donors: Leu-Leu (29.3%), Leu-Pro (52.1%) and Pro-Pro (18.6%), p = 0.006; resistant smokers: Leu-Leu (28.9%), Leu-Pro (51.3%) and Pro-Pro (19.7%), p = 0.02). The Pro 10 allele was less common in subjects with COPD (33%) than in blood donors (45%; OR = 0.62, 95% CI 0.45 to 0.86, p = 0.005) and resistant smokers (45%; OR = 0.59, 95% CI 0.40 to 0.88, p = 0.01). Conclusions: The proline allele at codon 10 of the TGF-β1 gene occurs more commonly in control subjects than in individuals with COPD. This allele is associated with increased production of TGF-β1 which raises the possibility that TGF-β1 has a protective role in COPD.